Toxic micro/nano particles removal in water via triboelectric nanogenerator. (September 2022) - Park, Byung-Geon; Lee, Cheoljae; Kim, Young-Jun; Park, Jinhyoung; Kim, Hyeok; Jung, Young; Ko, Jong Soo; Kim, Sang-Woo; Lee, Ju-Hyuck; Cho, Hanchul
Abstract: Herein, a new strategy for micro/nanoparticles removal in water using a triboelectric nanogenerator (TENG) is demonstrated. Removal process based on electrophoretic force can extract particles from water by its zeta potential due to the electric fields generated by the TENG, in other words, higher performance TENG removes more particles. High-performance TENG based on a three-dimensional porous-pyramid polydimethylsiloxane shows a power output nearly three times higher than that of a flat film-based TENG. With the proposed TENG, the removal rate is 21.4%, which is 5.6 times higher than that for the flat TENG (3.8%). By measuring the coverage area of the particles attached to the electrode, it was found that the removal of particles was significantly affected by the output voltage and operation time of the TENG. A TENG-driven self-powered electrophoretic system that removes sub-micron nanoparticles of polystyrene, CdSe/CdZnS, ZnO, and SiO2 is successfully demonstrated. Graphical Abstract: A self-powered micro/nanoparticles removal system based on electrophoresis with high output voltage triboelectric nanogenerator is introduced. Tons of nanoparticles what human have used can attack us by drinking the polluted water or eating the seafood. Through the removal system, our environment can be greener and our health will be improved. ga1 Highlights: A micro/nanoparticles removal system based on electrophoresis with high output voltage triboelectric nanogenerator. Proposed porous pyramid PDMS based TENGs generated 464 V which is 4 times higher than flat PDMS based TENGs. High performance TENGs removed the toxic particles 5.6 times more than flat one. Through the proposed removal process, plastic, heavy metal composite, ceramic and oxide material were successfully removed.